\(\frac{-5}{9}+\frac{8}{15}+\frac{-2}{11}...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 7 2016

p) \(\frac{-5}{9}+\frac{8}{15}+\frac{-2}{11}+\frac{4}{-9}+\frac{7}{15}\)

\(=\left(\frac{-5}{9}+\frac{-4}{9}\right)+\left(\frac{8}{15}+\frac{7}{15}\right)+\frac{-2}{11}\)

\(=-1+1+\frac{-2}{11}\)

\(=-\frac{2}{11}\)

q) \(\frac{5}{13}+\frac{-5}{17}+\frac{-20}{41}+\frac{8}{13}+\frac{-21}{41}\)

\(=\left(\frac{5}{13}+\frac{8}{13}\right)+\left(\frac{-20}{41}+\frac{-21}{41}\right)+\frac{-5}{17}\)


\(=1+\left(-1\right)+\frac{-5}{17}=\frac{-5}{17}\)

r) \(\frac{1}{5}+\frac{-2}{9}+\frac{-7}{9}+\frac{4}{5}+\frac{16}{17}\)

\(=\left(\frac{1}{5}+\frac{4}{5}\right)+\left(\frac{-2}{9}+\frac{-7}{9}\right)+\frac{16}{17}\)

\(=1+\left(-1\right)+\frac{16}{17}=\frac{16}{17}\)

21 tháng 6 2015

a,\(=\frac{-5}{9}+\frac{8}{15}+\frac{-2}{11}+\frac{-4}{9}+\frac{7}{15}\)

\(\left(\frac{-5}{9}+\frac{-4}{9}\right)+\left(\frac{8}{15}+\frac{7}{15}\right)+\frac{-2}{11}\)

=-1+1+-2/11

=0+-2/11

=-2/11

b,\(=\left(\frac{5}{13}+\frac{8}{13}\right)+\left(\frac{-20}{41}+\frac{-21}{40}\right)+\frac{-5}{17}\)

=1+-1+-5/17

=0+-5/17

=-5/17

c,\(=\left(\frac{1}{5}+\frac{4}{5}\right)+\left(\frac{-2}{9}+-\frac{7}{9}\right)+\frac{16}{17}\)

=1+-1+16/17

=0+16/17

=16/17

d,\(=\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+\frac{1}{7}-\frac{1}{9}+...+\frac{1}{99}-\frac{1}{101}\)

\(=\frac{1}{3}-\frac{1}{101}=\frac{98}{303}\)

 

a.\(\frac{-5}{9}\)+\(\frac{8}{15}\)+\(\frac{-2}{11}\)+\(\frac{4}{-9}\)+\(\frac{7}{15}\)

=\(\frac{-5}{9}\)+\(\frac{4}{-9}\)+\(\frac{8}{15}\)+\(\frac{7}{15}\)+\(\frac{-2}{11}\)

=(\(\frac{-5}{9}\)+\(\frac{-4}{9}\))+(\(\frac{8}{15}\)+\(\frac{7}{15}\))+\(\frac{-2}{11}\)

=(-1)+1+\(\frac{-2}{11}\)

=0+\(\frac{-2}{11}\)

=\(\frac{-2}{11}\).

 

7 tháng 3

bài 1 a)

\(\frac{15}{7}\times\frac43+\frac63\)

=\(\frac{60}{21}+\frac63\)

=\(\frac{60}{21}+\frac{42}{21}\)

=\(\frac{102}{21}\)

=\(\frac{34}{7}\)

7 tháng 3

b)\(\frac{-13}{41}\times\frac{17}{11}\times\frac{11}{17}\)

=\(\frac{-13}{41}\times\left(\frac{17}{11}\times\frac{11}{17}\right)\)

=\(\frac{-13}{41}\times1\)

=\(\frac{-13}{41}\)

3 tháng 3

\(\frac37+\frac{5}{13}+\frac{4}{13}\)

=\(\frac37+\left(\frac{5}{13}+\frac{4}{13}\right)\)

=\(\frac37+\frac{9}{13}\)

=\(\frac{39}{91}+\frac{63}{91}\)

=\(\frac{102}{91}\)

3 tháng 3

\(\left(\frac38+\frac{-3}{4}+\frac{7}{12}\right):\frac56+\frac12\)

=\(\left(\frac{9}{24}+\frac{-18}{24}+\frac{7}{24}\right)\times\frac65+\frac12\)

=\(\frac{5}{24}\times\frac65+\frac12\)

=\(\frac14+\frac12\)

=\(\frac14+\frac24\)

=\(\frac34\)

4 tháng 3

B1a)\(11\frac34-\left(6\frac56-4\frac12\right)+1\frac23\)

=\(11\frac34-6\frac56+4\frac12+1\frac23\)

=\(\left(11-6+4+1\right)+\left(\frac34-\frac56+\frac12+\frac23\right)\)

=\(10+\left(\frac{9}{12}-\frac{10}{12}+\frac{6}{12}+\frac{8}{12}\right)\)

=\(10+\left(-\frac{1}{12}+\frac{6}{12}+\frac{8}{12}\right)\)

=10+\(\frac{13}{12}\)

=\(\frac{120}{12}+\frac{13}{12}\)

=\(\frac{133}{12}\)

4 tháng 3

b)\(2\frac{17}{20}-1\frac{11}{5}+6\frac{9}{20}:3\)

= \(\frac{57}{20}-\frac{16}{5}+\frac{129}{20}\times\frac13\)

=\(\frac{57}{20}-\frac{16}{5}+\frac{129}{60}\)

=\(\frac{171}{60}-\frac{192}{60}+\frac{129}{60}\)

=\(\frac{108}{60}\)

=\(\frac95\)

3 tháng 6 2016

a/ 545/273

b/ 5/11

c/ -1

3 tháng 3

\(1\frac57-\frac57\times\frac{2}{11}-\frac57\times\frac{9}{11}\)

=\(\frac57\times\left(1-\frac{2}{11}-\frac{9}{11}\right)\)

=\(\frac57\times\left(\frac{11}{11}-\frac{2}{11}-\frac{9}{11}\right)\)

=\(\frac57\times1\)

=\(\frac57\)

3 tháng 3

\(\frac{5}{11}\times\frac{18}{29}-\frac{5}{11}\times\frac{8}{29}+\frac{5}{11}\times\frac{19}{26}\)

=\(\frac{5}{11}\times\left(\frac{18}{29}-\frac{8}{29}+\frac{19}{29}\right)\)

=\(\frac{5}{11}\times1\)

=\(\frac{5}{11}\)

4 tháng 3

bài 1b)

\(8\frac{1}{14}-6\frac37\)

C1:\(\frac{113}{14}-\frac{45}{7}\) =\(\frac{113}{14}-\frac{90}{14}=\frac{23}{14}\)

C2:\(8\frac{1}{14}-6\frac37=\left(8-6\right)+\left(\frac{1}{14}-\frac37\right)=2+\left(\frac{1}{14}-\frac{6}{14}\right)\)

\(=2+\frac{-5}{14}=\frac{28}{14}-\frac{5}{14}=\frac{23}{14}\)


4 tháng 3

bài 1 c)\(7-3\frac67\)

C1:\(\) \(7-3\frac67=7-\frac{27}{7}=\frac{49}{7}-\frac{27}{7}=\frac{22}{7}\)

C2:\(7-3\frac67=\left(7-3\right)-\frac67=4-\frac67=\frac{28}{7}-\frac67=\frac{22}{7}\)